De la rue Copernic au Quai d’Orsay : regards croisés sur la prise en charge des réfugiés espagnols en France (1945-1960) - Mélanie Trédez-Lopez (Cahiers de Civilisation Espagnole Contemporaine)
This study proposes to analyse the recognition process of Spanish refugees in France since 1945, when the French Government started to apply the Nansen international system to Spanish refugees while it hosted at the same time an important flow of Spanish migrants in its territory. The period of study ends in 1960 when the number of Spanish refugees registered in France began to decline. On the basis of an archives research at the Ministry of Foreign Affairs and at the French Office for the Protection of Refugees and Stateless Persons (ofpra), we will consider a cross-analysis of respective archives with a multifaceted approach: political, diplomatic, legal and administrative.This study also examines the French legal basis, the French-Spanish bilateral treaties (Jordana-Bérard Agreements) and the major international conventions on the protection of human rights.